Effectiveness and Safety of iStent Infinite Trabecular Micro-Bypass for Uncontrolled Glaucoma. Issue 1 (20th January 2023) - Sarkisian, Steven R.; Grover, Davinder S.; Gallardo, Mark J.; Brubaker, Jacob W.; Giamporcaro, Jane Ellen; Hornbeak, Dana M.; Katz, L. Jay; Navratil, Tomas; ,
Abstract : Précis: The iStent Infinite Trabecular Micro-Bypass System implanted in patients with open angle glaucoma (OAG) (uncontrolled by prior surgical or medical therapy) was effective in reducing mean diurnal intraocular pressure with a favorable safety profile. Purpose: The purpose of this study is to evaluate safety and effectiveness of the iStent infinite Trabecular Micro-Bypass System in patients with OAG uncontrolled by prior surgical or medical therapy. Design: Prospective, multicenter, single-arm, open-label clinical trial. Methods: Implantation of iStent infinite (3 iStent inject W stents) was performed as a stand-alone surgical procedure in eyes with OAG uncontrolled by prior incisional or cilioablative surgeries or maximum tolerated medical therapy (MTMT). Prospectively declared effectiveness endpoints were proportion of eyes achieving ≥20% mean diurnal intraocular pressure (MDIOP) reduction from baseline at month 12 on the same or fewer intraocular pressure (IOP)-lowering medication classes (responder endpoint) and mean change in MDIOP from baseline at month 12. Safety parameters included visual acuity, slit-lamp and fundus examinations, gonioscopy, perimetry, surgical complications, and adverse events. Results: Seventy-two eyes of 72 patients (mean age 71.9 y) with preoperative mean medicated MDIOP of 23.4±2.8 mm Hg on a mean of 3.1±0.9 IOP-lowering medication classes were enrolled: 61 eyes with failed prior surgery/ies (Failed-Surgery subgroup) and 11 eyes uncontrolled on MTMT (MTMT subgroup). A total of 76.1% of all enrolled patients met the responder endpoint (73.4% Failed-Surgery, 90.9% MTMT), with mean reduction (SE) in MDIOP at month 12 of 5.9(0.6) mm Hg [5.5(0.7) mm Hg Failed-Surgery subgroup, 8.1(0.9) mm Hg MTMT subgroup]. For patients on the same or fewer medication(s) as baseline, 53.0% achieved ≥30% MDIOP reduction without surgical interventions/other events. Safety was favorable, with no explants, infection, or device-related interventions or hypotony. Conclusions: iStent infinite stand-alone surgery achieved clinically significant IOP reduction and favorable safety in patients with OAG uncontrolled by prior therapy.